Simultaneous detection of infectious bronchitis virus and avian metapneumovirus genotypes A, B, and C by multiplex RT-qPCR assay in chicken tracheal samples in Ecuador - Loor-Giler, Anthony; Muslin, Claire; Santander-Parra, Silvana; Coello, Dayana; De la Torre, David; Abad, Hernán; Nuñez, Luis (Frontiers in Veterinary Science, 2024)
Respiratory RNA viruses such as Infectious bronchitis virus (IBV) and Avian metapneumovirus (aMPV), which are characterized by generating both respiratory damage and adverse effects on reproductive organs, affect poultry production economically due to high mortality rate and decrease in egg production and quality. Particularly, aMPV has three genotypes that have been reported with greater frequency in chickens: aMPV-A, aMPV-B, and aMPV-C. The present study proposes the design of a multiplex RT-qPCR assay for the simultaneous diagnosis of the 3 genotypes of interest of aMPV and IBV, followed by testing of 200 tracheal samples of vaccinated chickens with respiratory symptoms and finally a phylogenetic analysis of the sequences found. The assay detected up to 1 copy of each viral genome. The standard curves showed an efficiency between 90 and 100% in the multiplex assay and inter- and intra-assay coefficients of variation of 0.363 and 0.459, respectively and inter- and intra-assay coefficients of variation of 0.363 and 0.459, respectively. 69.5% of samples were found positive alone or in coinfection. 114 samples were positive for IBV, 13 for aMPV-A and 25 for aMPV-B. RNA of aMPV-C was no detected. The most commonly found combination was aMPV-B and IBV within 6 samples, and the least common was aMPV-A and aMPV-B in coinfection in 2 samples. The assay was specific for amplification of the genomes of the studied respiratory viruses (IBV, aMPV-A, aMPV-B, aMPV-C) as no amplification was shown from other viral genomes (ChPV, CAstV, ANV, and FAdV) or from the negative controls. Partial genomic Sanger sequencing enabled to identify circulating vaccine-derived and wild-type strains of IBV and vaccine and vaccine-derived strains of aMPV-B. In conclusion, this newly developed multiplex RT-qPCR was shown to be able to detect individual infections as well as co-infections among the respiratory viruses investigated. It was demonstrated to be a reliable and efficient tool for rapidly and safely diagnosing these infections. Furthermore, this study represents the first report of aMPV strains in Ecuadorian poultry and demonstrates the circulation of aMPV-A, aMPV-B, and GI-13 IBV strains in unvaccinated chicken populations in the country. Thus, it highlights the importance of simultaneously identifying these pathogens in greater detail and on a regular basis in Ecuador.